Explaining the Opportunities and Challenges of the Law on Dissemination and Free Access to Information in Iran from the Perspective of Lawyers - Yaghobi, Mohaddeseh (2021)
The right to have free access to information is one of the most underlying examples of the first generation of human rights. Also, it is a requirement of realization of citizenship rights and one of the vital issues in the principle of democratic participation discourse. Due to the importance of this issue, the approval of the Law on Dissemination and Free Access to Information in 2009 in Iran can be a vital step toward the achievement of free access to information, transparency, and favorable democracy. The purpose of this study is to explain the challenges and opportunities of the Law on Dissemination and Free Access to Information in Iran. Hence, by referring to scholars in the field of law, formal and natural evaluation of Law on Dissemination and Free Access to Information was done. The method in this study is data-based, and deep interviews are used to analyze the different aspects of this issue. The statistical population in this study consists of scholars and experts of the law. The results obtained from the interviews led to the identification of three opportunities including good democracy and governance, prevention and fight against corruption and revival and implementation of the citizenship document. Besides, five vital challenges were identified in the section of interviewing with lawyers: the ambiguity of law exceptions, lack of sanction of law, ambiguity in the concept of access to information, the challenge of dissemination system and access to information, and parallel laws challenges. According to the identified challenges and opportunities, it seems that the efforts of Ministries of Culture and Arts, Communications and Technology, Education, and National Media, and revision of legal articles concerning these challenges can be the proper solution to these problems.